Valoración de activos de la Empresa Ferticosta S. A. de la ciudad de Guayaquil, periodo 2021-2022. - Bermúdez Riera, Ambar Nicole (2023)
The valuation of assets within an organization is very important because it allows us to know the real situation of a company and helps to make financial and administrative decisions. The lack of this process represents not knowing the real financial situation of the organization and that limits executing correct decisions with respect to maintaining its continuity in the market, recapitalizing or undertaking any other option in the financial part. Therefore, it is essential that in every company a valuation is carried out. Reason for which, the objective of this case study is to value the assets of the company Ferticosta S. A of the city of Guayaquil, period 2021-2022. The research carried out has a quantitative approach with a descriptive and cross-sectional scope. The methods used are: inductive - deductive and book value method. While the techniques used for the acquisition of information were an analysis of documents because the Statements of Financial Position of the company Ferticosta S. A were observed, with the purpose of establishing the valuation of assets and an interview was also carried out. The results of the investigation concluded that: The values of the business asset registered in the Statement of Financial Position, both in the year 2021 and 2022 were $153,277.14 and $136,310.00 respectively; however, the values described do not represent the economic reality of the company, which reveals that there is inadequate management of accounting information.